RESULTS OF FORECASTING THE OIL RECOVERY FACTOR OF THE NORTH URTABULAK FIELD AT DIFFERENT RESERVOIR OPERATION MODES - Bobomurodov Utkir Ziyadullayevich (Scientific Trends, 2024)
Due to satellite oil gases, global warming, acid residues, climate change and the strengthening of the greenhouse effect are taking place.